Cocaine Bear [videorecording (DVD)] - Warden, Jimmy; Russell, Keri, 1976-; Jackson, O'Shea, Jr., 1991-; Convery, Christian, 2009-; Ehrenreich, Alden, 1989-; Ferguson, Jesse Tyler; Prince, Brooklynn, 2010-; Whitlock, Isiah, Jr; Hivju, Kristofer, 1978-; Hoekstra, Hannah, 1987-; Holliday, Aaron; Martindale, Margo, 1951-; et al. (Universal, 2023)
"An oddball group of cops, criminals, tourists, and teens congregate in a Georgia forest where a 500-pound black bear goes on a murderous rampage after accidentally ingesting cocaine." --